Charter and By-Laws of the City of New Haven, November, 1840 Title XI - Gunpowder Page 15 - (:unkn) unknown (General Publisher, 1827)
Prohibited, directly or indirectly, selling or delivering any gunpowder, or to have, store, or keep any quantity of gunpowder greater than one pound weight. The Court of Common Council shall have the power to license the sale, having, storing, and keeping gunpowder up to seven pounds in weight, and stored in a tin canister.
--
Keywords: GUN POWDER STORAGE